A Critical Mind Hanns Ullrich's Footprint in Internal Market Law, Antitrust and Intellectual Property - Godt, Christine; Lamping, Matthias (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2023)
This book traces the academic footprint of Hanns Ullrich. Thirty contributions revolve around five central topics of his oeuvre: the European legal order, competition law, intellectual property, the regulation of new technologies, and the global market order. Acknowledging him as a trailblazer, the book aims to capture how deeply Hanns Ullrich has influenced contemporaries and subsequent generations of scholars. The contributors re-iterate the path-breaking patterns of his teachings, such as his contemplation of intellectual property as embedded in competition, the necessity of balancing private and public interests in intellectual property law, the policies of market integration, and the peculiar relationship of technological advancement and protectionism. .
Part I: European Legal Order -- Market Access and Competition Rules of the EU - Was their Constitutionalization Based on a Judicial Error? -- Renewing the Van Gend Pledge - Continuity and Resilience in the Court's Construction and Defense of the Supranational Character of EU Law -- Why is the Regulation of Enforcement through the EU so Difficult? -- Part II: Competition -- On the Political Nature of Competition Law -- Competition Law and Political Influence of Large Corporations - How Antitrust Analysis Can Capture the Link between Political and Economic Institutions That Affect Market Competition -- Cutting into Diamonds: Competition Law, IPR, Trade Secrets and the Case of 'Big Data' -- FRAND Declarations and the 'Third-Party Effect' - A Contract Law and Competition Law Perspective -- In Rem Effect of Licensing Declarations - Hanns Ullrich's Traces in Recent Case Law -- Part III: Intellectual Property -- Mapping the Intangible Economy -- Exclusive Rights for a Purpose - Intellectual Property as a Framework Regulation of Innovation Markets -- From a Rights-Based to a Procedural Approach: Re-Purposing the Exercise of Intellectual Property Rights -- How to Stay Modern Feudalism? Comparing EU and US Methodologies in Containing Post-Sale Restraints by Way of IP Exhaustion -- Virtual Patent Networks and Their Network Effects -- The Public Interest in Compulsory Licensing: Examining the Complementarity Between IP and Competition Law -- Part IV: Data Economy -- Digital Sovereignty and Governance in the Data Economy: Data Trusteeship instead of Property Rights on Data -- Incentives for Data-Sharing as a Case on (Regulating) Knowledge Externalities -- Some Remarks on the Subjective Profiles of the EOSC Project, Especially from the Perspective of IP Law -- Part V: Artificial Intelligence -- Inventorship in the Age of Artificial Intelligence -- Artificial Intelligence and the Technicality Requirement of Patent Law -- Patent Infringement by Development and Use of Artificial Intelligence Systems, Specifically Artificial Neural Networks -- Part VI: Digital Media -- Copyright, News, and 'Information Products' under the New DSM Copyright Directive -- Media, Legal Tech and Modern Copyright Law German Lawyers in the Digital World -- Media Policy and Copyright in Europe: The Progressive Expansion of the Law for Broadcasters to Online Platforms -- Part VII: Biotechnology -- Gene Editing Technology Patents or Monopolization of Scientific Knowledge and Health Care? -- A Comprehensive Approach to Plant Variety Rights and Patents in the Field of Innovative Plants -- Part VIII: Global Market Order -- TRIPS through a Military Looking Glass -- A Transactional Approach to Intellectual Property -- Manufacturing for Export: A TRIPS-Consistent Pro-Competitive Exception -- Reductionist Intellectual Property Protection and Expansionist (and 'Prodevelopment') Competition Rules as a Human Rights Imperative? Enhancing Technology Transfer to the Global South -- Caught Between Post- and Neo-Colonialism - IP for Traditional Knowledge, Traditional Cultural Expressions and Indigenous Resources.
Keywords: Information technology -- Law and legislation; Mass media -- Law and legislation; IT Law, Media Law, Intellectual Property